15-(6-g)=

Simple and best practice solution for 15-(6-g)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15-(6-g)= equation:


Simplifying
15 + -1(6 + -1g) = 0
15 + (6 * -1 + -1g * -1) = 0
15 + (-6 + 1g) = 0

Combine like terms: 15 + -6 = 9
9 + 1g = 0

Solving
9 + 1g = 0

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + 1g = 0 + -9

Combine like terms: 9 + -9 = 0
0 + 1g = 0 + -9
1g = 0 + -9

Combine like terms: 0 + -9 = -9
1g = -9

Divide each side by '1'.
g = -9

Simplifying
g = -9

See similar equations:

| 2(x+2)-6=3x-19 | | x+14(2x+16)= | | h(1.7)=82-4.9(2.89) | | -9x+12=-3(3x-4) | | -2d+5=0 | | 6x+12-14=6x-2 | | Y=1/2x-4-4 | | 7+d=37 | | x^2+7=16 | | 4(2x+8)=3(3x+11) | | 9x(7x-8)=92 | | 34+8x=-18 | | 2(w-4)-4=-3(-7w+6)-4w | | 18.53+18c=-15.5c-19.28-12.44 | | -2(y+5)=8y-30 | | 9/9x | | -10h-2=-9h+1+7 | | 80/-5 | | .5x+2.6x=x+39 | | 10x^2-12x-24=0 | | -2+5x+9=6(x+2)-4 | | 4.2n=-4.16+n | | 2+6d=-8+7d | | 80+40=180 | | (8x10)/-5 | | -7b=-6b+9 | | 6.5y-18.66=14.02+8.4y | | 28=(-13)+x | | 5/×=1 | | 17=k/2 | | X+-11=7x+-13 | | 3+7n=87-5n |

Equations solver categories